2020
DOI: 10.3390/mi11050535
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Prosthetic Approaches to Enhance Visual Perception for Blind Patients

Abstract: Retinal prostheses are implantable devices that aim to restore the vision of blind patients suffering from retinal degeneration, mainly by artificially stimulating the remaining retinal neurons. Some retinal prostheses have successfully reached the stage of clinical trials; however, these devices can only restore vision partially and remain insufficient to enable patients to conduct everyday life independently. The visual acuity of the artificial vision is limited by various factors from both engineering and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 186 publications
(236 reference statements)
0
21
0
Order By: Relevance
“…Another matter relating to mechanical properties of our implantable multi-electrode array components in particular was the channel count needed in order to be able to stimulate sufficient numbers of sites to have a reasonable likelihood of restoring “useful” vision. We estimated for our third-generation retinal prosthesis that at least 256 channels would be required, based on the findings of a number of teams in the field over the last 20+ years that have recently been reviewed [ 3 , 4 ]. Since no de-multiplexer was included in our system in a distal region near the stimulation sites beneath the retina, this meant that >256 individual traces or leads would need to be incorporated along the length of the array from the stimulator package containing the circuitry, to the electrode locations within the eye.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another matter relating to mechanical properties of our implantable multi-electrode array components in particular was the channel count needed in order to be able to stimulate sufficient numbers of sites to have a reasonable likelihood of restoring “useful” vision. We estimated for our third-generation retinal prosthesis that at least 256 channels would be required, based on the findings of a number of teams in the field over the last 20+ years that have recently been reviewed [ 3 , 4 ]. Since no de-multiplexer was included in our system in a distal region near the stimulation sites beneath the retina, this meant that >256 individual traces or leads would need to be incorporated along the length of the array from the stimulator package containing the circuitry, to the electrode locations within the eye.…”
Section: Methodsmentioning
confidence: 99%
“…In that case, it was the limitations of the fabrication process for creating high temperature co-fired ceramic parts that determined the spacing. While it is true that high channel counts can and have been achieved, e.g., by the use of alternative, photodiode-based visual prosthesis designs, those approaches are entirely different, make use of the capabilities of silicon foundries used to create such devices, and have been reviewed elsewhere [ 3 , 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For future innovations in retinal prosthetics, comprehensive understanding of the current status is essential. In that sense, the review paper of Shim et al [ 6 ] is timely. They have systematically compared a broad array of existing methodologies for retinal stimulation.…”
mentioning
confidence: 99%
“…In microelectronic approaches, stimulating electrodes have long been in two-dimensional planar shapes which typically touch the epi-/sub-retinal surface. Recently, these planar electrodes have been challenged by three-dimensional (3D) electrodes in diverse shapes [ 6 , 8 , 9 ]. In this Special Issue as well, the two articles by Shire et al and Seo et al [ 10 , 11 ] reported 3D pillar electrode structures.…”
mentioning
confidence: 99%